The analysis of the pyroptosis-related genes and hub gene TP63 ceRNA axis in osteosarcoma - Han, Jun; Hu, Yunxiang; Ding, Shengqiang; Liu, Sanmao; Wang, Hong (Frontiers in Immunology, 2022)
Pyroptosis is a type of programmed cell death that is associated with tumor development, prognosis, as well as therapeutic response. The significance of pyroptosis related genes (PRGs) in tumor microenvironment (TME) remains unclear. We examined the expression patterns of PRGs in 141 OS samples from 2 different datasets and characterized the genetic and transcriptional changes in PRGs. Based on these PRGs, all OS samples could be classified into two clusters. We discovered that multi-layer PRG changes were linked to clinicopathological traits, prognosis, and TME characteristics in two separate genetic subtypes. The PRG score was then developed for predicting overall survival and its predictive efficacy in OS patients was tested. As a result, we developed a very precise nomogram to improve the PRG predictive model in clinical application. Furthermore, a ceRNA network was built to find a LAMTOR5-AS1/hsa-miR-23a-3p/TP63 regulatory axis. Through experimental verification, it was found that the pyroptosis gene TP63 plays an important role in the regulation of osteosarcoma pyroptosis. The possible functions of PRGs in the TME, clinicopathological characteristics, and prognosis were established in our investigation of PRGs in OS. These findings may aid in our understanding of PRGs in OS, as well as provide a novel way for prognostic evaluation and the creation of more effective immunotherapy treatments.